Effects of Weaning Age and Antibiotic Use on Pig Performance in a Commercial System - J. E. Faccin; M. W. Allerson; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; S. S. Dritz; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 2,184 barrows and gilts (DNA 600 × PIC L42) were used in a study from weaning to market to evaluate the effect of increasing weaning age and antibiotic use on pig performance in a commercial production system. A 3 × 2 factorial arrangement was used. The treatments included weaning age (18.5, 21.5, or 24.5 days of age) and the use of antibiotic (AB) or antibiotic free (ABF). There were 14 replicate pens per treatment and 26 pigs per pen (13 barrows and 13 gilts). Pigs were weaned from a 4,000-sow farm and placed in pens by weaning age with pens randomly assigned to AB or ABF. Pigs assigned to AB had access to a diet containing 400 ppm of chlortetracycline (CTC) from d 8 to 21 post-weaning, and after a porcine respiratory and reproductive syndrome (PRRS) outbreak at week 7 post-weaning, they were medicated via drinking water for five consecutive days with CTC (10 mg/lb of body weight (BW) per day). For the first 42 days post-weaning, increasing weaning age reduced the number of pigs treated with injectable antibiotic (quadratic,P= 0.004), but AB use did not influence this variable (P= 0.626). Each additional day of weaning age resulted in greater BW at weaning and at 197 days of age with slopes of 0.484 lb and 1.485 lb, respectively (linear,P<0.001). From weaning to 197 days of age, increasing weaning age increased average daily gain (0.02 lb/day of weaning age; linear,P<0.001) and the same effect was found for AB (0.03 lb/d;P= 0.009). Weaning age and AB also affected average daily feed intake (0.03 lb/day of increase in weaning age; linear,P<0.001 and 0.08 lb/d;P= 0.031, respectively). An interaction (linear,P= 0.005) was found for feed efficiency. When AB were fed, pigs weaned at 21.5 and 24.5 d were less efficient. However, AB improved feed efficiency of pigs weaned at 18.5 d. Pigs with access to AB in feed and water had lower total losses (2.7% less mortality + removal;P<0.001). Increasing weaning age also marginally decreased total losses (-0.21% per day increase in weaning age; linear,P= 0.097). The weight sold (at 197 d of age) per pig weaned was increased by increasing weaning age (an additional 1.55 lb for each day increase in weaning age; linear,P= 0.050) and by using AB in feed and water (an addition of 10.1 lb/pig;P= 0.019). In summary, increasing weaning age linearly improved pig performance and relatively short-term use of antibiotics reduced mortality and removals. In addition, both factors contributed to maximizing the weight sold per pig weaned.
Keywords: weaning age; antibiotic; growth; swine